2020
DOI: 10.1111/jne.12883
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signalling to somatotrophs: Transcriptional and post‐transcriptional mediators

Abstract: In normal individuals, pituitary somatotrophs optimise body composition by responding to metabolic signals from leptin. To identify mechanisms behind the regulation of somatotrophs by leptin, we used Cre-LoxP technology to delete leptin receptors (LEPR) selectively in somatotrophs and developed populations purified by fluorescence-activated cell sorting (FACS) that contained 99% somatotrophs. FACSpurified, Lepr-null somatotrophs showed reduced levels of growth hormone (GH), growth hormone-releasing hormone rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Metabolic disorders are associated with disordered levels of miRNA production and secretion (reviewed in [ 83 ]). Specifically, leptin has been shown to modulate miRNA levels (see [ 84 , 85 , 86 , 87 ] for a few recent examples), and we have demonstrated this in somatotropes [ 88 ]. Since our in silico analyses predicted binding sites for miRNAs within the 3′UTR of Gnrhr ( Table 1 ), we wished to determine whether or not leptin may regulate Gnrhr post-transcriptionally via regulation of gonadotrope miRNA levels.…”
Section: Metabolic Influences On the Post-transcriptional Regulatimentioning
confidence: 81%
“…Metabolic disorders are associated with disordered levels of miRNA production and secretion (reviewed in [ 83 ]). Specifically, leptin has been shown to modulate miRNA levels (see [ 84 , 85 , 86 , 87 ] for a few recent examples), and we have demonstrated this in somatotropes [ 88 ]. Since our in silico analyses predicted binding sites for miRNAs within the 3′UTR of Gnrhr ( Table 1 ), we wished to determine whether or not leptin may regulate Gnrhr post-transcriptionally via regulation of gonadotrope miRNA levels.…”
Section: Metabolic Influences On the Post-transcriptional Regulatimentioning
confidence: 81%
“…We continued the investigation of leptin signaling pathways in somatotropes and reported that they included both transcriptional and posttranscriptional regulators [3]. Our tests of pathway inhibitors showed that full GH expression may be maintained by leptin through the JAK/STAT3 pathway but not nitric oxide.…”
Section: Leptin Regulation Of Somatotropesmentioning
confidence: 92%
“…This contrasts with leptin pathways that regulate gonadotropins, which include NOS. Leptin regulation is likely to be transcriptional as loss of LEPR in somatotropes reduced Gh and Ghrhr mRNA and proteins [3]. In addition, leptin regulation of the Pou1f1 transcription factor may also serve as a pathway for the transcriptional regulation of Gh and Ghrhr [2,3,60].…”
Section: Leptin Regulation Of Somatotropesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hypothalamic regulation, peripheral signals also regulate GH and prolactin production and release, although the mechanism of many of these is poorly understood. Cell‐specific manipulation of receptor expression can provide insights into this, as is demonstrated in the study by Allensworth‐James et al, 9 who show that the decreased GH secretion following loss of leptin receptors specifically in GH‐secreting somatotrophs is mediated by alterations in both gene transcription and translation. Key mediators in the regulation of prolactin have also been identified in fish, where prolactin has an osmoregulatory role 10 .…”
mentioning
confidence: 95%